Seedling emergence and herbage yield of summer‐active tall fescue sown at different times and sowing depths - Beribe, Maria Jose; Barletta, Pablo Fernando; Scheneiter, Jorge Omar (Wiley, 2025)
Background: Tall fescue is sensitive to sowing depth and, in the Pampas region of Argentina, its sowing is often delayed from autumn (average air temperature 18.5°C) to winter (average air temperature 10.0°C). Since tall fescue is sensitive to the sowing depth, and temperature determines the emergence period, this study aimed to evaluate the effect of sowing depth at different times on seedling emergence and herbage yield. Methods: Two field experiments were carried out in Pergamino, Buenos Aires province, Argentina, to evaluate a summer-active tall fescue at two sowing times and five sowing depths. The emergence of seedlings and the herbage yield in the year of sowing were determined. Results: Seedling emergence was maximal when sown at 1.2–1.5 cm depth and at 230 growing degree days (GDD) in early autumn and 257 GDD in winter. In both years and sowing seasons, herbage yield was positively related to the number of seedlings at maximum emergence. Conclusions: No differences in seedling emergence were observed between the autumn and winter sowings, and the emergence of tall fescue was well explained by the thermal time. The concept of “critical depth” was determined as the sowing depth at which the greatest seedling emergence and forage yield are achieved.